Comparison of potential habitat of genus rhaphidopora in Kelantan based on different qualitative methods. - Nor Syahirah Mohd Ruzi (2017)
The lowland forest in Malaysia especially in Kelantan has been exploited by logging activity and this can cause land use change. Thus the consequences from this activity can cause habitat loss of flora mostly dipterocarps. The mapping species distribution has become an important tools for conservation because an early prediction can be made using environmental and species occurrence data. This study was conducted to compare potential habitat of selected species of genus Rhaphidopora in Kelantan based on different qualitative methods. Furthermore, the qualitative methods that used in this study is Maximum Entropy (MAXENT), Area of Occupancy (AOO) and Extent of Occurrence (EOO). MAXENT model is widely used as a tool to determine the conservation assessment by using locality data and environmental data such as bioclimatic variable, soil database and altitudinal data. For conservation analysis, Ecological Niche Modelling (ENM) is broadly used because it accuracy. The selected species are Rhaphidopora falcata, Rhaphidopora maingayi and Rhaphidopora korthalsii and the locality data are obtained from the secondary sources. The result shows the comparison of percentage distribution for the selected species. The percentage distribution of Rhaphidopora falcata for AOO is 0.32%, EOO is 43.6 % and for ENM is 19.28%. For percentage distribution of Rhaphidopora maingayi, AOO is 0.51%, EOO is 62.09% and for ENM is 3.80 %.The percentage of distribution for Rhaphidopora korthalsii for AOO is 0.45%, EOO is 62.95% and for ENM is 12.07%. Thus, EOO methods shows the overestimates distribution of the species while AOO shows underestimates the species distribution and MAXENT shows intermediate distribution of the species. Hence, from this study shows that ENM is better compared to AOO and EOO by using MAXENT software which is it more suitable to be used as rapid assessment tool for regional conservation assessment.